Diseño de un mortero hidráulico, utilizando cemento blanco como aglomerante de los agregados - Salvatierra Espinoza, Alex Bolívar (2021)
The analysis and results of designing a Hydraulic Mortar elaborated with white cement as binder of the aggregates exposed in this article, was carried out in order to give to the Construction Industry a different alternatives for preparing mortars, either for gluing blocks, plastering masonry or to make moldings. For the design of the mortar, sand from the Boliche river, white cement, water and additive were used. It is important to mention that the sand was subjected to the granulometric test when the fineness modulus and the absorption test were determined; with these parameters the dosage of white cement for the experimental procedure started, water was added at 25°C, which met the temperatura determined in the ASTM C172 standard. The workability of the mortar could be maintained due to the control of the water-cement ratio below A/ C=0.50, where a high range water reducing additive was used for this purpose. The resistance obtained after the compression tests reached the expectations, since white cement provides greater resistance to compression and with a ratio of 1: 1.50 has an average at 28 days of more than 140 Kg/cm2 greater than the one given by a dosage and time than that of gray cement.